A facile approach to prepare Bi(OH)3 nanoflakes as high-performance pseudocapacitor materials. (27th August 2015) - Zhang, Wei; Huang, Xiaoxiong; Tan, Yueyue; Gao, Yilong; Wu, Jianxiang; Hu, Jinbo; Stein, Andreas; Tang, Bohejin
<x xml:space="preserve">Abstract</x> Bi(OH)3 nanoflakes deliver a specific capacitance of 888 F g−1 at a current density of 1 A g−1.